1999
DOI: 10.1177/0272989x9901900106
|View full text |Cite
|
Sign up to set email alerts
|

A Practice Pathway for the Initial Diagnostic Evaluation of Isolated Sixth Cranial Nerve Palsies

Abstract: The recommendations of the practice pathway are supported by review of the literature and the retrospective review of these cases. However, a prospective study with a matched control group is needed to demonstrate regional and specialty-specific variations in care and to strengthen the clinical certainty of the pathway recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 56 publications
0
23
0
1
Order By: Relevance
“…Nonetheless, the role for immediate neuroimaging (without a 3-to 4-month observation period) in patients z 50 years of age remains controversial [1,[11][12][13]26]. While follow-up without immediate neuroimaging may result in cost reduction in the evaluation of many patients [26], a substantial proportion of patients in our cohort (14%-all aged z 50 years) had etiologies that, if identified, would alter immediate patient management (i.e., immunomodulatory therapy for first demyelinating event; high-dose corticosteroids to prevent Addisonian crisis in pituitary apoplexy; MR angiography, echocardiography, and immediate initiation of antiplatelet therapy or anticoagulation for brainstem infarct; and immediate evaluation and control of blood pressure in the setting of hypertensive brainstem hemorrhage). In fact, some patients with brainstem infarcts and isolated third nerve palsies [22] or other isolated or minimal neurologic deficits [31,32] have been demonstrated to have cardiac sources of emboli or large vessel thromboembolic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the role for immediate neuroimaging (without a 3-to 4-month observation period) in patients z 50 years of age remains controversial [1,[11][12][13]26]. While follow-up without immediate neuroimaging may result in cost reduction in the evaluation of many patients [26], a substantial proportion of patients in our cohort (14%-all aged z 50 years) had etiologies that, if identified, would alter immediate patient management (i.e., immunomodulatory therapy for first demyelinating event; high-dose corticosteroids to prevent Addisonian crisis in pituitary apoplexy; MR angiography, echocardiography, and immediate initiation of antiplatelet therapy or anticoagulation for brainstem infarct; and immediate evaluation and control of blood pressure in the setting of hypertensive brainstem hemorrhage). In fact, some patients with brainstem infarcts and isolated third nerve palsies [22] or other isolated or minimal neurologic deficits [31,32] have been demonstrated to have cardiac sources of emboli or large vessel thromboembolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…These include serious and potentially treatable disorders, such as intra-axial and extraaxial neoplasms, demyelinating disease, brainstem infarcts, and pituitary apoplexy [9 -24]. Despite such reports in the literature, the need for immediate neuroimaging in patients aged 50 years and older (age group in which microvascular nerve ischemia commonly occurs) remains controversial [1,2,9,12,25,26]. Retrospective analyses of large series have suggested that follow-up without immediate neuroimaging in patients with suspected microvascular ischemia may save costs; however, authors of these practice pathways have also emphasized the need for prospective studies [26].…”
Section: Introductionmentioning
confidence: 99%
“…7 Miller et al 8 suggested that careful follow-up is necessary for these cases, and neuroimaging should be considered when spontaneous recovery is absent or new neurological symptoms appear. In cases with spontaneous recovery, no abnormal lesions responsible for the nerve palsy are usually found even by the updated MRI sequences.…”
Section: Discussionmentioning
confidence: 99%
“…14,19 The vulnerability of this nerve is usually ascribed to its long intracranial course, since, after emerging at the pontomedullary sulcus, it runs up to the orbit, where it innervates the lateral rectus muscle. 7 The presence of points of fixation along its course, its tortuosity, and its tight attachment to the skull base also contribute to the nerve's vulnerability.…”
Section: ©Aans 2013mentioning
confidence: 99%